The arpeggione and fortepiano of the 1820s in the context of current computer music. - Mogensen, René; Deletaille, Nicolas; Roudier, Alain (Early Music, 2014)
Arpeggione soloist Nicolas Deletaille has collaborated with pianist Alain Roudier and composer René Mogensen in a project with the intent of reinventing the musical thinking for the arpeggione, in the context of contemporary computer music. For this project, Mogensen composed two new works for arpeggione and computer, which brought together 1820s performance practice with current interactive computer music. The project toured in Belgium, Denmark, France and Italy, and culminated in a CD release of new works.In this report we give some background information, and briefly introduce some analytical tools to help ground understanding of the musical context. We then focus on discussion of several performance practice problems, and the solutions to these problems which we developed during our work on this collaborative project. These problems and solutions are indicative of a performance practice that is specific to the combination of acoustic instruments and computer sound in chamber music. We found that the results of the project were artistically successful, giving rich experiences both for performers and audiences.